Digest: Species delimitation in the face of demographic processes. (6th January 2020) - Peede, David; D'Agostino, Emmanuel; Ottenburghs, Jente
Abstract: Existing approaches to species delimitation use the extent of divergence between taxa. However, processes, such as gene flow during divergence or secondary contact, as well as population expansion and migration, complicate this task. Smith and Carstens introduce the R package delimitR, which uses machine learning to integrate gene flow into species delimitation inference.